Investigating nanoplastics toxicity using advanced stem cell-based intestinal and lung in vitro models - Busch, Mathias; Brouwer, Hugo; Aalderink, Germaine; Bredeck, Gerrit; Kämpfer, Angela A. M.; Schins, Roel P. F.; Bouwmeester, Hans (Frontiers in Toxicology, 2023)
Plastic particles in the nanometer range–called nanoplastics–are environmental contaminants with growing public health concern. As plastic particles are present in water, soil, air and food, human exposure via intestine and lung is unavoidable, but possible health effects are still to be elucidated. To better understand the Mode of Action of plastic particles, it is key to use experimental models that best reflect human physiology. Novel assessment methods like advanced cell models and several alternative approaches are currently used and developed in the scientific community. So far, the use of cancer cell line-based models is the standard approach regarding in vitro nanotoxicology. However, among the many advantages of the use of cancer cell lines, there are also disadvantages that might favor other approaches. In this review, we compare cell line-based models with stem cell-based in vitro models of the human intestine and lung. In the context of nanoplastics research, we highlight the advantages that come with the use of stem cells. Further, the specific challenges of testing nanoplastics in vitro are discussed. Although the use of stem cell-based models can be demanding, we conclude that, depending on the research question, stem cells in combination with advanced exposure strategies might be a more suitable approach than cancer cell lines when it comes to toxicological investigation of nanoplastics.